Understanding Employee Performance: Policy, Culture, and Job Satisfaction in Hospitals - Saputra, Riski Novian Indra; Suciningtias, Marlyn; Irawati, Jovita (Jurnal Minds: Manajemen Ide dan Inspirasi, 2026)
This study examines how policy implementation and organizational culture shape employee performance through job satisfaction in a Type C hospital in Central Java. It contributes to the literature by clarifying how policy execution and cultural mechanisms jointly translate into performance outcomes via everyday satisfaction processes in healthcare settings. Using a qualitative design, data were collected from six informants across service units and analyzed through thematic techniques. Findings indicate that clear and consistently communicated policies enhance task clarity and motivation, whereas poorly socialized changes generate uncertainty and workload strain. A collaborative culture reinforces positive behaviors and organizational attachment, while job satisfaction emerges from interpersonal relations, recognition, facilities, and balanced workloads. These dynamics position satisfaction as a central mediating mechanism linking structural and cultural factors to performance. The findings imply that hospitals should strengthen policy socialization, recognition systems, and collaborative culture to sustain employee performance.